Method for producing compound fertilizer by melting urea fertilizer with heat conducting oil heated cyclically and granulating in high tower - HUANG LANYU (2012)
The invention discloses a method for producing a compound fertilizer by melting urea with heat conducting oil heated cyclically and granulating in a high tower, wherein urea fertilizer meltwater is used as a fluid carrier, is intensively mixed with powdery monoammonium phosphate, potassium chloride or lemery salt, and auxiliary materials in a mixing tank to form slurry, the slurry is dispersed into small liquid drops by a granulating device at the top of a granulating tower, the small liquid drops drop under the effect of the gravity and the buoyancy force, reversely contact cold air from thebottom of the granulating tower to be cooled and solidified and finally freely drop to form compound fertilizer particles by cooling and solidifying. The main point of the method is that the preparation of the urea fertilizer meltwater comprises the following steps of: adding the urea fertilizer into a urea fertilizer melting pot, adding 150-160 DEG C heat conducting oil in the coil pipe of the urea fertilizer melting pot